Proof: Log Product Rule
Let's prove the following theorem:
This theorem allows us to convert a log of a product to a sum of the log of each operand.
For example:
log2(8 ⋅ 16) = (log28) + (log216)
log2(8 ⋅ 16) = 3 + 4
log2(8 ⋅ 16) = 7
Before calculators were invented, multiplying large numbers would take a long time. People used the Log Product Rule to convert multiplication problems to addition problems which are easier to solve.
Let's try multiplying two numbers using the following algorithm:
- Calculate log base 10 of both operands using a log table.
- Add the results.
- Calculate 10 to the power of the result from step 2 using an "anti-log" table.
For example, suppose we want to calculate 14⋅18.
First, we calculate:
log10(14 ⋅ 18)
This is equal to
(log1014) + (log1018)
Then, the log table tells us that:
log1014 = 1.146
log1018 = 1.255
Thus:
(log1014) + (log1018) = 2.401
Finally, the anti-log table tells us that:
102.401 = 251.77
14⋅18 = 252, so we came quite close to the answer.
The key to proving this theorem is the following exponentiation property:
xm ⋅ xn = x(m+n)
Proof:
1 | logbx = m |
---|---|
2 | logby = n |
3 | logb(x ⋅ y) = o |
# | Claim | Reason |
---|---|---|
1 | bm = x | if logbx = m, then bm = x |
2 | bn = y | if logby = n, then bn = y |
3 | bo = x ⋅ y | if logb(x ⋅ y) = o, then bo = x ⋅ y |
4 | bo = (bm) ⋅ (bn) | if bm = x and bn = y and bo = x ⋅ y, then bo = (bm) ⋅ (bn) |
5 | (bm) ⋅ (bn) = b(m + n) | (bm) ⋅ (bn) = b(m + n) |
6 | bo = b(m + n) | if bo = (bm) ⋅ (bn) and (bm) ⋅ (bn) = b(m + n), then bo = b(m + n) |
7 | o = m + n | if bo = b(m + n), then o = m + n |
8 | logb(x ⋅ y) = (logbx) + (logby) | if logbx = m and logby = n and logb(x ⋅ y) = o and o = m + n, then logb(x ⋅ y) = (logbx) + (logby) |
Comments
Please log in to add comments